'Are we there yet?' Australian HR professionals and the Fourth Industrial Revolution. (31st August 2019) - Nankervis, Alan; Connell, Julia; Cameron, Roslyn; Montague, Alan; Prikshat, Verma
Abstract : Although still in its early stages, the Fourth Industrial Revolution (FIR), which involves a broad range of artificial intelligence, robotics and machine learning technologies, will fundamentally change the way many of us work and relate to one another. Driven by technology, this transformation presents a range of challenges, as well as opportunities, where we might expect Human Resource (HR) professionals would lead the way. However, little is currently known in relation to how prepared HR professionals in Australia are to ready their organisations for this new era of work and associated resourcing. Consequently, this paper goes some way towards closing that gap. Specifically, the study reported here sets out to explore the levels of preparedness amongst Australian HRM professionals for the impact of the FIR on organisations, workplaces, jobs and skills, as well as on their own professional roles and competencies. The study utilised a sequential mixed methods research design with two phases, the first was qualitative focus groups ( n  = 5) followed by a quantitative online survey of selected senior HR practitioners ( n  = 150). The findings indicate that, while most believe that FIR technologies might be useful for their organisations and assist with improving job performance, increasing productivity and making jobs easier for employees, contrarily many did not intend to use them in the foreseeable future. Marginal support was also evident in relation to the potential contributions of FIR technologies to HR process enhancement and overall HR effectiveness. Most respondents were also not impressed with the lack of current Australian government FIR strategies and policies. Key points: Organisations differ in their development stages. Similarly, there is divergence amongst Australian HR professionals with respect to their understanding of the likely impacts of the Fourth Industrial Revolution, and their preparedness for them. HR professionals' skills, capabilities and competencies need to be upgraded. Governments and professional associations also need to become better prepared to address the challenges.